Powerful Lipolytic Activity of Fungi Isolated from Coconut and Avocado Flesh on Different pH and Temperature - Prapti Sedijani; Dewa Ayu Citra Rasmi; Kusmiyati Kusmiyati; Riska Agustina Anggriani (Jurnal Penelitian Pendidikan IPA, 2021)
Lipase is widely applied in various fields of industries elevating its economic value. The demand for lipase keeps increasing open up working opportunities. Isolates showing lipolytic activity obtained previously are tested for their activity on different pH mediums: 7, 8, 9, and 10; and at different temperatures. The fungi are grown on SDA medium supplemented with Olive Oil, emulsifier, Tween 80, and Rhodamine B. The experiment was made in 3 replicates and is incubated at room temperature of 30oC. Lipase activity was calculated based on the clear zone around colonies observed on day 2 and day 3 after inoculation. The result shows that those isolates are highly active on various pH at RT, and the activity slightly reduces at 30oC. This result suggests that a wide range of their applications are at room temperature when pH is a limiting factor for the applications